A autopercepção do aluno e da família sobre as dificuldades de escrita em uma escola pública de Araguaina. - Melo, Loriana Soares da Silva Arruda (Universidade Federal do Tocantins, 2022)
Learning to write is fundamental to a child's social and emotional development, as well as being a knowledge base for other subjects. Failure to learn writing leads to numerous difficulties and problems ranging from social exclusion to a sense of disability. Thus, the work aims to verify the self-perception of students and their families about their writing difficulties. The qualitative research was conducted in an 8th grade class of a public school in Araguaína / TO, five students who identified themselves through a questionnaire as having difficulties to write, and one family member was invited to talk about their children's difficulties, that is, five children and five parents participated in the research. For data collection with the children, a semi-directed, recorded and transcribed interview was used. They were asked to draw a picture that represented writing difficulties and to write a story about what it is like to have writing difficulties. With the parents a semi-directed interview was conducted. For the analysis of the results we used the technique of drawing analysis and for the interviews content analysis. As a result, children demonstrate to know the importance of learning written language and its social function, demonstrate to be literate, but with great difficulties in using the standard language. They also show by their drawings and stories that they suffer from the situation and feel inferior. Regarding parents, there is still little participation in the child's universe at school and about their child's learning. It is concluded that children realize that they are affected by their difficulties and that parents, despite recognizing the importance of writing, participate little in school life.